Government-Use License and Stem Cell-Based Pharmaceuticals Patent: Equitable Access to Covid-19 Medications - RAHMAH, R. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In response to the outbreak of the Covid-19 pandemic, some pharmaceutical companies have patented their drugs to combat it, including those based on stem cells. Questions about how to access such drugs will likely be raised because patent protection grants an exclusive right to the patent owner, to prevent someone else from benefiting from a large-scale price increase. The document will then review the regulation and practice of government use in Indonesia and the possibility of such a mechanism to access Covid-19 drugs.RESUMEN En respuesta al brote de la pandemia Covid-19, algunas compañías farmacéuticas han patentado sus medicamentos para combatirlo, incluidos aquellos basados en células madre. Probablemente se plantearán preguntas sobre cómo acceder a dichos medicamentos porque la protección de la patente otorga un derecho exclusivo al titular de la misma, para evitar que otra persona pueda beneficiarse con un aumento de precio a gran escala. Luego, el documento revisará la regulación y la práctica del uso gubernamental en Indonesia y la posibilidad de dicho mecanismo para acceder a los medicamentos Covid-19.